2013
DOI: 10.1002/cbic.201300424
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New N‐Acylhomoserine Lactone Signalling Compounds of Dinoroseobacter shibae DFL‐12T by Overexpression of luxI Genes

Abstract: Bacteria of the Roseobacter clade are widespread in the ocean and occur in many different habitats. In the genome of Dinoroseobacter shibae DFL-12, luxI homologous genes that encode synthases responsible for the formation of N-acylhomoserine lactones (AHLs) have been described. These compounds are known autoinducers that regulate several biological traits-namely, flagella formation and cell differentiation-in D. shibae through quorum sensing. The AHLs produced by D. shibae mainly consisted of N-octadecadienoyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 24 publications
2
48
0
Order By: Relevance
“…The constitutive heterologous expression of each synthase in a non-AHL-producing E. coli resulted in the production of long-chain AHLs (Supplementary Figure S1). GC-MS analysis (Neumann et al, 2013) showed that when expressed in E. coli, the main compound produced by LuxI 1 was the wild-type signal C18en-HSL. In addition, small amounts of C16-HSL, C15-HSL and C14-HSL were found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The constitutive heterologous expression of each synthase in a non-AHL-producing E. coli resulted in the production of long-chain AHLs (Supplementary Figure S1). GC-MS analysis (Neumann et al, 2013) showed that when expressed in E. coli, the main compound produced by LuxI 1 was the wild-type signal C18en-HSL. In addition, small amounts of C16-HSL, C15-HSL and C14-HSL were found.…”
Section: Resultsmentioning
confidence: 99%
“…As the deletion of only one synthase leads to a complete loss of AHL production, the contribution of LuxI 2 and LuxI 3 to AHL synthesis in D. shibae appears to be dependent on the presence and level of the signal molecules provided by LuxI 1 . The wild-type signals C18en-HSL and C18dien-HSL were strongly overproduced in the D. shibae DluxI 1 strain carrying pDP1, and thus it was possible to purify these novel signals and determine their absolute configuration (Neumann et al, 2013). Both C18en-HSL and C18dien-HSL were then chemically synthesized and their effect on the phenotype and transcriptome of the DluxI 1 deletion strain was studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While roseobacters are known to produce long-chain AHLs with various degrees of oxidation and side-chain saturation (11,30,34,35,46), the full complement of AHLs synthesized by lineage members and the contribution of these chemical signals to roseobacter ecology are not yet known. Here we identified a novel AHL, 3OHC 12:1 -HSL, in Phaeobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, bacteria possessing luxIR homologs produce and release AHLs into the external environment (7). At high cell densities, AHL concentrations can reach a threshold concentration, bind to the corresponding cognate cytoplasmic LuxR proteins, and affect transcription of various genetic loci (8)(9)(10)(11). AHLs have also been shown to activate regulators other than the corresponding cognate LuxR, suggesting that cross talk may play an important role in intra-and interspecies interactions (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%